Derivation and validation of cutoffs for clinical use of cell cycle arrest biomarkers - Hoste, Eric A J; McCullough, Peter A; Kashani, Kianoush; Chawla, Lakhmir S; Joannidis, Michael; Shaw, Andrew D; Feldkamp, Thorsten; Uettwiller-Geiger, Denise L; McCarthy, Paul; Shi, Jing; Walker, Michael G; Kellum, John A (Nephrology, dialysis, transplantation, 2014)
Acute kidney injury (AKI) remains a deadly condition. Tissue inhibitor of metalloproteinases (TIMP)-2 and insulin-like growth factor binding protein (IGFBP)7 are two recently discovered urinary biomarkers for AKI. We now report on the development, and diagnostic accuracy of two clinical cutoffs for a test using these markers. We derived cutoffs based on sensitivity and specificity for prediction of Kidney Disease: Improving Global Outcomes Stages 2-3 AKI within 12 h using data from a previously published multicenter cohort (Sapphire). Next, we verified these cutoffs in a new study (Opal) enrolling 154 critically ill adults from six sites in the USA. One hundred subjects (14%) in Sapphire and 27 (18%) in Opal met the primary end point. The results of the Opal study replicated those of Sapphire. Relative risk (95% CI) in both studies for subjects testing at ≤0.3 versus >0.3-2 were 4.7 (1.5-16) and 4.4 (2.5-8.7), or 12 (4.2-40) and 18 (10-37) for ≤0.3 versus >2. For the 0.3 cutoff, sensitivity was 89% in both studies, and specificity 50 and 53%. For 2.0, sensitivity was 42 and 44%, and specificity 95 and 90%. Urinary [TIMP-2]•[IGFBP7] values of 0.3 or greater identify patients at high risk and those >2 at highest risk for AKI and provide new information to support clinical decision-making. Clintrials.gov # NCT01209169 (Sapphire) and NCT01846884 (Opal).